2015
DOI: 10.1016/j.otsr.2015.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Is knee function better with contemporary modular bicompartmental arthroplasty compared to total knee arthroplasty? Short-term outcomes of a prospective matched study including 68cases

Abstract: III, case-control study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Otherwise, modular “off-the-shelf” implants using unicondylar implants combined with a patellofemoral implant are required. However, controversy still exists regarding the functional outcomes when compared to TKA [ 23 , 31 ]. To date, scarce data are available on the treatment of bicompartmental osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, modular “off-the-shelf” implants using unicondylar implants combined with a patellofemoral implant are required. However, controversy still exists regarding the functional outcomes when compared to TKA [ 23 , 31 ]. To date, scarce data are available on the treatment of bicompartmental osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 6 studies were selected for inclusion in the meta-analysis, as shown in the PRISMA flow diagram ( Fig. 1 ) [13] , [14] , [15] , [16] , [17] , [18] . A kappa value of 0.9 was determined based on the selections of two reviewers (S. K. and H.…”
Section: Resultsmentioning
confidence: 99%
“… Study Design Level Implant N Age Gender (female:male) BMI Follow-Up, y Complications Revisions BKA TKA BKA TKA BKA TKA BKA TKA BKA TKA BKA TKA Parratte et al. 2015 [13] Pseudorandomized IIA Modular 34 34 61 (7) 61 (8) 21:13 21:13 27.5 (4) 27.5 (4.5) 3.8 (1.7) 0 1 0 1 Yeo et al. 2015 [16] RCT I Modular 22 20 63.8 (8.03) 63.1 (7.34) 21:5 16:6 27.28 (3.04) 28.15 (4.52) 6 m, 1, 2, 5 1 0 1 0 Engh et al.…”
Section: Resultsmentioning
confidence: 99%
“…Short-term result of modular BKR is good, [4][5][6][7][8] with most studies showing similar or better function than TKR. 9,10 Other advantages include less blood loss, 11,12 better gait pattern, and knee kinematics [13][14][15][16] as BKR is more bone/ ligament preserving than TKR. However, there is still no conclusion whether it is a worthwhile procedure when compared to UKR and TKR in the long run, in terms of clinical outcome, survivorship, and late complications.…”
Section: Discussionmentioning
confidence: 99%